As relações Brasil–Estados Unidos no governo Clinton: a intersecção entre o debate teórico e a análise de política externa nas relações internacionais - Santos, Aline Pavan dos [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
A década de 1990 representa um marco no Sistema Internacional pelo fim da bipolaridade que atingiu tanto as potências como os países que pertenciam ao Terceiro Mundo. Neste contexto, pretende-se destacar o estudo das relações Brasil x EUA a fim de identificar os elementos da agenda de cada um dos países isoladamente e a projeção destes nas relações bilaterais. De modo complementar propõe-se uma incursão sobre as teorias de relações internacionais desenvolvidas à época a fim de verificar se as abordagens que surgem neste período são capazes de fundamentar solidamente a constituição do Sistema Internacional neste novo momento, bem como, as relações dos países destacados para estudo

International negotiations under the climate change gain prominence in recent years. There are growing concerns about environmental disasters on the planet, causing global impacts. International efforts to curb climate change policy framework are carried out with the United Nations (UN), inside the Framework Convention on Climate Change (UNFCCC). Brazil has over the years played an important role in the negotiations, being the host country on the establishment of the Convention, during the Rio-92. In recent years the Lula da Silva government, it has established the resumption of domestic climate policies and also the continuity of effective participation in international negotiations. During the Copenhagen Conference, Brazil assumed as a goal emission reductions, but voluntarily. However, the country has always been opposed to these goals. The central theme of our research is to analyze the evolution of Brazilian foreign policy in the global climate negotiations. It aims the understanding the of a set of factors, both internal and external, that have influenced the evolution of foreign Brazilian policy climate
Keywords: Clinton, Bill - 1946-; Cardoso, Fernando Henrique - 1931-; Neoliberalismo; Política Interncaional - Séc. XX; Globalização; Estados Unidos - Relações exteriores; Brasil - Relações exteriores